The Celtici from Gallaecia: notes on ethnicity and territoriality in the NW Iberian Peninsula during the Iron Age - González García, Fracisco Javier (Complutum, 2011)
This paper discusses in the first place two stereotypes of the research on the Iron Age of NW Iberian Peninsula: the refusal of Celtic ethnicity for some pre-roman peoples and the rejection of the historical evidence available from Greek and Roman texts. Secondly, this paper tries to show that some material evidence may be used to delimit inner areas within the archaeological record of NW Iberian Peninsula as well as to define different ethnicities.
Keywords: NW Iberian Peninsula; Iron Age; Ethnicity; Celts